Butterfly Pea Flower (Clitoria ternatea) Biocompability as an Oral Healthcare Biomaterial: A Narrative Literature Review - Daffa Satria Faadihilah; I Gusti Aju Wahju Ardani; Tengku Natasha Eleena binti Tengku Ahmad Noor; Alexander Patera Nugraha (Indonesian Journal of Dental Medicine, 2025)
Background: Natural biomaterials are increasingly explored in dentistry due to concerns regarding cytotoxicity and adverse effects of synthetic agents. Butterfly pea flower (Clitoria ternatea) has demonstrated antimicrobial, antioxidant, and anti-inflammatory properties, suggesting potential application in oral health care. Purpose: This review aims to evaluate current evidence regarding the biocompatibility of C. ternatea as an oral health care biomaterial. Review: A literature search was conducted using Scopus-indexed databases for studies published from 2020 onwards. Ten studies were included. The reviewed literature consistently demonstrated significant antimicrobial and antibiofilm activity of C. ternatea against major oral pathogens. Concentration-dependent antioxidant and anti-inflammatory effects were also reported. However, none of the included studies directly evaluated cytotoxicity or cell compatibility with oral cells such as gingival fibroblasts, oral epithelial cells, or dental pulp cells. Conclusion: C. ternatea shows promising biological activity for oral health applications; however, current evidence is insufficient to establish its biocompatibility as an oral biomaterial. Further studies assessing cytotoxicity and cellular responses of oral tissues are essential before clinical translation.